Preferensi Masyarakat Terhadap Potensi Maskot Wisata di Kota Sukabumi Provinsi Jawa Barat - Kurnia, Insan; Munajat, Chery Pixy Redaniar; Untari, Rini (Jurnal Ilmiah Ilmu Pariwisata, 2023)
The mascot is the personification of an object that you want to represent and has important value in tourism as part of city branding. The mascot is related to regional identity and is widely known by the public. The research aims to identify the potential of maskots and people's preferences for mascots in Sukabumi City. The research was conducted in February-June 2021 with the stages of (1) identifying potential maskots, (2) direct observation, and (3) identifying preferences through a questionnaire with a likert scale of 1-4 from 263 respondents from the people of Sukabumi City. There were 30 potential mascot objects identified, consisting of 12 culinary objects, eight building objects, seven flora objects, and three transportation objects. All of these objects can still be found and are in the Sukabumi City. Overall, the highest preference for tourism mascot potential was mochi (?????=3.75; n=256) while the lowest was the Post Office (?????=2.48; n=192).